Hannah (Schooner : 1780-1783) bill of lading - Hannah (Schooner : 1780-1783)
Bill of lading together with testimony concerning the Atlantic shipping trade of the schooner, Hannah, in the litigation of John Banks vs. Smith & Bowdoin.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Banks, John, -- active 1780-1783.; Smith & Bowdoin; Bills of lading -- United States; Shipping -- United States -- History -- 18th century; Ship's papers -- 18th century